USING KIT FOR KIDS AT DISCOVERY LEARNING MODEL TO INCREASE INTEREST TOWARD SCIENCE ELEMENTARY SCHOOL STUDENTS - Setiawan, Sigit (PrimaryEdu : Journal of Primary Education, 2021)
AbstractThis research was conducted to determine the increase in interest at elementary school students through the use of kits for kids in the discovery learning model. The research method used is a quasi-experimental research design with the matching only pretest and posttest control group design. The learning process in the experimental class applies a kit for kids-assisted discovery learning model, while the control class applies traditional learning. The learning took place for two meetings, both in the experimental class and in the control class. Each learning process is carried out by observing the implementation of learning activities. The research subjects were 23 students in the experimental class and 22 students in the control class. The research instrument uses an attitude scale for interest in science. The attitude scale of interest in science was modified from the Attitude Toward Science in School Assessment (ATSSA) which measured aspects of interest in science or science learning (interest in science). The data analysis technique of each student's interest attitude scale towards Science was answered to get a score of 1 and those who were not answered were not given a score for each statement. The results showed that the data analysis of the student's interest in science attitude scale in the experimental class showed a better improvement after receiving discovery learning treatment using kit for kids compared to students in the control class who received traditional learning treatment.Keywords: discovery learning, kit for kids, interest in scienceAbstrakPenelitian ini dilakukan untuk mengetahui peningkatan minat terhadap Sains siswa SD melalui penggunaan kit for kids pada model discovery learning. Metode penelitian yang digunakan adalah eksperimen semu dengan desain penelitian the matching only pretest and posttest control group design. Proses pembelajaran pada kelas eksperimen menerapkan model discovery learning berbantuan kit for kids sedangkan pada kelas kontrol menerapkan pembelajaran tradisional. Pembelajaran berlangsung selama dua pertemuan, baik pada kelas eksperimen maupun pada kelas kontrol. Setiap pembelajaran dilaksanakan proses observasi keterlaksanaan kegiatan pembelajaran. Subjek penelitian pada kelas eksperimen 23 siswa dan pada kelas kontrol 22 siswa. Instrumen penelitian menggunakan skala sikap untuk minat terhadap Sains. Skala sikap minat terhadap Sains dimodifikasi dari Attitude Toward Science in School Assessment (ATSSA) yang mengukur aspek minat terhadap Pembelajaran IPA atau Sains (interest in science). Teknik analisis data setiap skala sikap minat terhadap Sains siswa yang dijawab memperoleh skor 1 dan yang tidak dijawab tidak diberikan skor untuk setiap pernyataannya. Hasil penelitian menunjukkan bahwa analisis data skala sikap minat terhadap sains siswa di kelas eksperimen menunjukkan peningkatan yang lebih baik setelah mendapatkan perlakuan pembelajaran discovery menggunakan kit for kids dibandingkan dengan siswa di kelas kontrol yang mendapatkan perlakuan pembelajaran tradisional.Â Kata kunci: discovery learning, kit for kids, minat terhadap sains